2022
DOI: 10.1111/ajco.13876
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharide of Lactobacillus casei SB27 reduced colon cancer cell prognosis through mitochondrial damage by upregulation of HINT2

Abstract: AimsColorectal cancer (CRC) is one of the most common malignant tumors worldwide. This study aimed to explore the effects of Polysaccharide of Lactobacillus casei SB27 in colon cancer and its possible mechanisms.MethodsColon cancer was induced by giving dextran sulfate sodium and Azoxymethane. Uman Colon Cancer Cell Line (HCT)‐116 cells were used to vitro model in this experiment.ResultsPolysaccharide of L. casei SB27 reduced colon cancer in azoxymethane‐dextran sulfate sodium (AOM+DSS)‐induced mice. Polysacch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Current evidence suggests that COA6 is associated with tumor progression and signi cant adverse survival in patients with lung cancer, hepatocellular carcinoma, and colon cancer [47][48][49]. Moreover, HINT2 (histidine triad nucleotide-binding protein 2) is extensively involved in cell energy metabolism [50] and the pathogenesis of various malignant tumors, such as endometrial and colorectal cancer [51,52]. It has been found that HINT2 could induce apoptosis of tumor cells through mitochondrial-related pathways and also played an important role in promoting tumor proliferation and migration by downregulating the expression of HINT2, thus leading to poor prognosis of patients [53].…”
Section: Discussionmentioning
confidence: 99%
“…Current evidence suggests that COA6 is associated with tumor progression and signi cant adverse survival in patients with lung cancer, hepatocellular carcinoma, and colon cancer [47][48][49]. Moreover, HINT2 (histidine triad nucleotide-binding protein 2) is extensively involved in cell energy metabolism [50] and the pathogenesis of various malignant tumors, such as endometrial and colorectal cancer [51,52]. It has been found that HINT2 could induce apoptosis of tumor cells through mitochondrial-related pathways and also played an important role in promoting tumor proliferation and migration by downregulating the expression of HINT2, thus leading to poor prognosis of patients [53].…”
Section: Discussionmentioning
confidence: 99%
“…The preliminary evidence of the inflammation-reducing effects of EPS-J12 has been established. However, further research is required to determine whether it exerts an anticancer effect, whether it is regulated through a signalling pathway, and whether it exerts an effect on mitochondria 34 or is associated with the growth and spread of cancerous cells 35 .…”
Section: The Expression Level Of Il-12amentioning
confidence: 99%
“…In a recent report by Di et al . (2023), it was revealed that the EPS of L. casei SB27 effectively reduces colon cancer cells. So, the primary objective of our study was to concentrate on the production of camel milk yoghurt, using probiotic bacteria isolated from dairy products, that had the capability to produce higher quantities of EPS.…”
Section: Introductionmentioning
confidence: 98%